2021
DOI: 10.3389/fimmu.2021.664371
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated IL-32 Expression And Reduced Gut Short Chain Fatty Acid Caproic Acid in People Living With HIV With Subclinical Atherosclerosis

Abstract: Despite the success of antiretroviral therapy (ART), people living with HIV (PLWH) are still at higher risk for cardiovascular diseases (CVDs) that are mediated by chronic inflammation. Identification of novel inflammatory mediators with the inherent potential to be used as CVD biomarkers and also as therapeutic targets is critically needed for better risk stratification and disease management in PLWH. Here, we investigated the expression and potential role of the multi-isoform proinflammatory cytokine IL-32 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 64 publications
4
24
0
Order By: Relevance
“…De Preter et al [49] reported a higher value of hexanoic acid in a control group compared with patients with Inflammatory Bowel Disease. Hexanoic acid also exerted a potential positive role as immune system modulator in the regulation of Interleukin-32, an important cytokine involved in inflammation and cancer development [50]. These data are also in line with our findings, which reported a negative correlation between hexanoic acid and the worsening of gastrointestinal clinical symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…De Preter et al [49] reported a higher value of hexanoic acid in a control group compared with patients with Inflammatory Bowel Disease. Hexanoic acid also exerted a potential positive role as immune system modulator in the regulation of Interleukin-32, an important cytokine involved in inflammation and cancer development [50]. These data are also in line with our findings, which reported a negative correlation between hexanoic acid and the worsening of gastrointestinal clinical symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…It is reported that the contents of propionic acid, butyric acid, iso-butyric acid, and valeric acid evidently decreased in the colonic contents in DSS-induced colitis mice, which is quite consistent with our results ( 36 ). Caproic acid shows anti-inflammatory effect for its reduction in NF-κB transactivation and decrease in inflammatory cytokine production ( 37 , 38 ). More importantly, fecal levels of caproic acid have been shown to inversely correlate with Crohn's disease activity ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cells in inflamed gut tissue are described as having a 27-fold higher frequency of HIV DNA than cells in non-inflamed gut tissue (110). This immune activation and inflammation is thought to lead to an increase in the frequency of other conditions such as metabolic and cardiovascular diseases (111).…”
Section: Intestinal Barrier Functionmentioning
confidence: 99%